2021
DOI: 10.3389/fimmu.2021.630358
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Perspectives of RNA N6-methyladenosine (m6A) Modification on Immunity and Autoimmune Diseases

Abstract: N6-methyladenosine (m6A) modification, the addition of a methylation decoration at the position of N6 of adenosine, is one of the most prevalent modifications among the over 100 known chemical modifications of RNA. Numerous studies have recently characterized that RNA m6A modification functions as a critical post-transcriptional regulator of gene expression through modulating various aspects of RNA metabolism. In this review, we will illustrate the current perspectives on the biological process of m6A methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“…The N 6 -methyladenosine (m6A) modification, which is the most abundant conserved post-translational modification, is found in a wide range of cellular RNAs. In recent years, m6A modifications have been shown to have an important function in the progression of various metabolic, 1 infectious, 2 immune system, 3 and cardiovascular diseases 4 and cancers. 5 The RNA base sequence DRACH (D = A/G/U, R = A/G, H = A/C/U) is the consensus site of m6A.…”
Section: Introductionmentioning
confidence: 99%
“…The N 6 -methyladenosine (m6A) modification, which is the most abundant conserved post-translational modification, is found in a wide range of cellular RNAs. In recent years, m6A modifications have been shown to have an important function in the progression of various metabolic, 1 infectious, 2 immune system, 3 and cardiovascular diseases 4 and cancers. 5 The RNA base sequence DRACH (D = A/G/U, R = A/G, H = A/C/U) is the consensus site of m6A.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, m6A modification interferes with RNA recognition (Karikó et al, 2005). Viruses can use m6A modification to escape host immune recognition because of the presence of widely distributed m6A modifications in viral mRNA (Tang et al, 2021). In addition, mounting evidence has demonstrated m6A modifications in viral RNA (Durbin et al, 2016;Lu et al, 2020), host circRNAs (Chen et al, 2019), and normal endogenous ssRNA (Gao et al, 2020).…”
Section: Physiological Role Of M6a Rna Modificationmentioning
confidence: 99%
“…RNA methylation affects tumor biology by regulating the relevant components of the immune system. It has been found that m 6 A RNA methylation has a variety of biology-regulatory functions during the occurrence and development of cancers via modulating tumor immunity ( 75 , 78 , 79 ). The TIME is often characterized by the infiltration of various immunosuppressive cell types, most notably MDSCs and Tregs, and a lack of antitumor immune activity ( 8 , 80 ).…”
Section: Associations Of M 6 a Rna Methylation With Tumor Immunity In Various Cancersmentioning
confidence: 99%